Alternative Grounding Method Using Coconut Shell Charcoal as Media of Mesh Electrodes - Moch Dhofir; Rini Nur Hasanah; Hadi Suyono; Avrizal Riva Belan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
The utilization of coconut charcoal as alternative media of grounding was investigated. The mesh-electrode was made of stainless steel of 8-mm diameter, whereas its lattice dimension was 50cmx50cm. Four variations of lattice number were considered, i.e. 1-, 2-, and 4-lattice structures. Dry and wet charcoal media were considered. Mesh location was fixed in the depth of 80cm under the ground, while the 10cm of medium thickness variation was chosen. The resistance obtained using 10-cm thickness of charcoal layer in a mesh consisting of 1-, 2-, and 4-lattices were 268, 131, and 78 ohms consecutively. The addition of layer up to 80-cm resulted in a resistance decrease of 48%, 33%, and 44%. Using wet charcoal, the 10-cm layer produced 26.5, 17.5, and 14.8 ohms of grounding resistance and a reduction of 25%, 10%, and 3.6% subsequently for 1-, 2-, and 4-lattice mesh structure if the layer thickness was 80 cm.